2012
DOI: 10.1093/jac/dks372
|View full text |Cite
|
Sign up to set email alerts
|

The silver cation (Ag+): antistaphylococcal activity, mode of action and resistance studies

Abstract: The rapid and extensive loss of membrane integrity observed upon challenge with Ag(+) suggests that the antibacterial activity results directly from damage to the bacterial membrane. The universal susceptibility of staphylococci to Ag(+), and failure to select for resistance to Ag(+), suggest that silver compounds remain a viable option for the prevention and treatment of topical staphylococcal infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
95
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(103 citation statements)
references
References 43 publications
8
95
0
Order By: Relevance
“…Rather, resistance to silver is a by-product of copper resistance and cadmium is a by-product of zinc resistance. In fact, resistance studies with S. aureus were unable to produce silver-resistant strains even after 42 days of continuous passage in the presence of AgNO 3 (Randall et al 2013) Similar results were observed for some Gram-negative organisms, whereas in E. coli strains, silver resistance arises as a result of mutations in both ompR and cusS or mediated through the sil system (Randall et al 2015).…”
Section: Copper and Zinc Resistance In Gram-positive Bacteriasupporting
confidence: 55%
“…Rather, resistance to silver is a by-product of copper resistance and cadmium is a by-product of zinc resistance. In fact, resistance studies with S. aureus were unable to produce silver-resistant strains even after 42 days of continuous passage in the presence of AgNO 3 (Randall et al 2013) Similar results were observed for some Gram-negative organisms, whereas in E. coli strains, silver resistance arises as a result of mutations in both ompR and cusS or mediated through the sil system (Randall et al 2015).…”
Section: Copper and Zinc Resistance In Gram-positive Bacteriasupporting
confidence: 55%
“…Silver resistance so far is only known in Gram-negative bacteria. Especially in staphylococci, which are the most frequent pathogen in IAIs, we intended to induce silver resistance by performing serial exposure to subinhibitory silver concentrations (37). Among others, we chose staphylococci with putative potential of silver resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Due to these promising results, we asked the question of whether exposure to silver could induce resistance in staphylococci. If so, it would abolish the efficacy of silver-containing implants, but so far no silver resistance has been observed in Gram-positive bacteria (35)(36)(37). Hence, we exposed seven staphylococcal clinical isolates and ATCC strains (MSSE 1457, MRSE ATCC 35984, MSSA ATCC 13420, MRSA ATCC 43300, copper-resistant S. aureus ATCC 12600, and MRSA USA300 and its putative ⌬SilE mutant-all exhibiting an AgNO 3 MIC of 15.6 or 31.2 g/ml) to subinhibitory concentrations of silver and performed serial passaging via daily subculturing.…”
Section: (C) (D and E) Prevention Rates For Silver-coated (Open Columentioning
confidence: 99%
“…Clinical investigations into the anti-bacterial nature of such silver-containing dressings have revealed the potent activity against Pseudomonas aeruginosa, vancomycin-resistant Pseudomonas species and methicillin-resistant Staphylococcus aureus (MRSA) (Ulker et al, 2005;Olsen et al, 2000). Silver has been widely used in the treatment of S. aureus infections and one of its primary modes of action has been suggested to involve disruption of bacterial membrane integrity (Randall et al, 2013). Other clinical benefits of silver wound dressings include a reduction in wound associated pain (Rustogi et al, 2005), increased epithelialisation of skin grafts (Demling and Desanti, 2002) and increased efficiency at preventing MRSA colonisation of burn wounds (Honari et al, 2011).…”
Section: Introductionmentioning
confidence: 99%